Pemanfaatan Digital Marketing untuk Komunikasi Bisnis UMKM di Desa Sumber Rejo Kabupaten Batubara Sumatera Utara - Utami, Rizkika; Alindra, Devi Alvionita; Siregar, Feby Yoana; Purba, Christin Agustina; Anggoro, Muhammad Agung (Sekolah Tinggi Ilmu Manajemen Sukma Medan, 2025)
The utilization of digital technology is a key factor in enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in the global economic era. This community service research aims to empower MSME actors in Sumber Rejo Village, Batubara Regency, North Sumatra, through the optimization of digital marketing as a means of business communication. The partners consist of 26 MSMEs producing